2021
DOI: 10.1002/art.41686
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Mobile App to Monitor Patient‐Reported Outcomes in Rheumatoid Arthritis: A Randomized Controlled Trial

Abstract: Objective. To examine the effects of a smartphone application (app) to monitor longitudinal electronic patientreported outcomes (ePROs) on patient satisfaction and disease activity in patients with rheumatoid arthritis (RA).Methods. We conducted a 6-month randomized controlled trial of care coordination along with an app (intervention) versus care coordination alone (control) in 191 RA patients. Participants in the intervention group were prompted to provide information daily using ePROs. In both the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 34 publications
0
47
1
Order By: Relevance
“…While health care utilization dropped, no difference was found in patient-physician interaction, health care satisfaction, self-efficacy, or treatment satisfaction between the intervention and control groups. The lack of improvement following an intervention using a smartphone app in these outcomes was also found by Lee et al (14) but contrasts with other studies (15,17,34). In our study, the secondary outcome measures were already at favorable levels at baseline, which suggests that patients with low disease activity value the current system of face-to-face consultations, which has been previously described (35).…”
Section: Discussioncontrasting
confidence: 97%
“…While health care utilization dropped, no difference was found in patient-physician interaction, health care satisfaction, self-efficacy, or treatment satisfaction between the intervention and control groups. The lack of improvement following an intervention using a smartphone app in these outcomes was also found by Lee et al (14) but contrasts with other studies (15,17,34). In our study, the secondary outcome measures were already at favorable levels at baseline, which suggests that patients with low disease activity value the current system of face-to-face consultations, which has been previously described (35).…”
Section: Discussioncontrasting
confidence: 97%
“…15 Importantly, not all patients have access, skills or interest in using remote digital solutions. 16 Although previous studies (mainly explorative or outside rheumatology) have demonstrated feasibility of electronic systems for online data entry of PROs, [17][18][19][20][21][22][23][24] no studies have to our knowledge explored use following large-scale routine care implementation of a nationwide online system in IRD.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Although high adherence to reporting ePRO’s through mobile applications (apps) was observed in recently performed trials that investigated telemonitoring, often adherence declined over time reducing the potential benefits [ 7 9 ]. For example, adherence decreased from 88 to 62% during the 6 month study of Lee et al [ 10 ]. In addition, Seppen et al reported declining adherence rates from > 90% in week one, to less than 50% in week four [ 11 ].…”
Section: Introductionmentioning
confidence: 99%